THE IMPACT OF CONTRASTING EVENTS STRATEGY ON MOTOR SATISFACTION AND LEARNING PERFORMANCE OF VOLLEYBALL BLOCKING SKILL FOR SECOND-STAGE COLLEGE STUDENTS - Asst. Lecturer Hayder Hasan Karam (Galaxy International Interdisciplinary Research Journal, 2023)
The aim of this study was to investigate the effect of the contrasting events strategy on motor satisfaction and learning performance of the volleyball blocking skill for second-stage college students in the College of Physical Education at the University of Al-Qadisiyah. The research emphasizes the importance of utilizing modern teaching strategies in teaching sports skills, as they enhance students’ motor skills and contribute to their development while reducing the effort required from teachers. The research problem identified a weakness in students’ performance of the volleyball blocking skill due to the prevalent use of traditional teaching methods that prioritize the teacher’s role and neglect the active participation of students in improving their skills. The researcher conducted an experimental study using two groups, with the research community consisting of second-stage college students in the College of Physical Education at the University of Al-Qadisiyah for the academic year 2022-2023, with a total of 135 students. The research sample included 36 students, divided into two groups, where the experimental group learned using the contrasting events strategy, while the control group learned using the traditional method employed by the teacher. The researcher concluded that the contrasting events strategy was more effective than the traditional method in enhancing motor satisfaction and learning performance of the volleyball blocking skill for students. One of the main recommendations is to adopt this strategy to enhance students’ learning and performance in the volleyball blocking skill.